2013
DOI: 10.1152/ajprenal.00643.2012
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin ameliorates podocyte injury in advanced diabetic nephropathy in thedb/dbmouse

Abstract: Podocyte damage and accumulation of advanced glycation end products (AGEs) are characteristics of diabetic nephropathy (DN). The pathophysiology of AGE-challenged podocytes, such as hypertrophy, apoptosis, and reduced cell migration, is closely related to the induction of the cell cycle inhibitor p27(Kip1) and to the inhibition of neuropilin 1 (NRP1). We have previously demonstrated that treatment with erythropoietin is associated with protective effects for podocytes in vitro. db/db mice with overt DN aged 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Erythropoietin protected mouse podocytes from damage by advanced glycation end-products [7]. Furthermore, erythropoietin ameliorated podocyte injury in advanced diabetic nephropathy in the db/db mouse [8]. In humans, serum erythropoietin transiently increased from baseline in the dapagliflozin group up to week 4, followed by a gradual decline until week 12 [9].…”
Section: To the Editormentioning
confidence: 99%
“…Erythropoietin protected mouse podocytes from damage by advanced glycation end-products [7]. Furthermore, erythropoietin ameliorated podocyte injury in advanced diabetic nephropathy in the db/db mouse [8]. In humans, serum erythropoietin transiently increased from baseline in the dapagliflozin group up to week 4, followed by a gradual decline until week 12 [9].…”
Section: To the Editormentioning
confidence: 99%
“…EPO and leptin share some structural similarities as members of the class-I cytokine superfamily and both signal through JAK/STAT pathways. EPO treatment in db / db mice was reported to promote VEGF expression, which could stimulate angiogenesis, and improved wound healing, stimulated podocyte survival, and, particularly with low dose administration, reduced albuminuria and diabetic kidney damage [152,153,154]. EPO treatment in db / db mice was also reported to reduce damage in cardiomyopathy, inhibiting transforming growth factor-β (TGF-β) and activating AKT signaling pathways as observed in kidney, and reduce injury to insulin producing pancreatic β-cells via antiapoptotic, anti-inflammatory and angiogenic effects in the islets [154,155,156].…”
Section: Epo Regulation Of Metabolism and Obesitymentioning
confidence: 99%
“…Several studies have demonstrated that HIF signalling protects the kidney against AKI [30,76,[78][79][80][81]. In addition, increasing evidence suggests that EPO has organ protective effects, which may be useful in the prevention of renal disease [82][83][84]. For example, renoprotective effects of EPO have been shown in IR injury via activation of the Akt/ endothelial NOS -dependent pathway and in DN via amelioration of podocyte damage [80,84].…”
Section: Renoprotective Effects Of Hypoxia-inducible Factors and Erytmentioning
confidence: 99%